Niger : Second and Third Reviews Under the Extended Credit Facility Arrangement and Requests for Waivers of Nonobservance of Performance Criteria and for Extension of the Program Period and Arrangement, Rephasing of Disbursements, and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Niger's Second and Third Reviews Under the Extended Credit Facility (ECF) Arrangement and Requests for Waivers of Nonobservance of Performance Criteria and for Extension of the Program Period and Arrangement. Fiscal performance was broadly in line with program targets. The medium-term outlook appears favorable, with robust growth benefiting from important natural resource sector investments. However, the outlook is vulnerable to high domestic and external risks, including potential spillovers from the security situation in the region and climatic shocks. The IMF staff recommends the completion of the second and third reviews under the ECF.